2011
DOI: 10.1007/s10493-011-9481-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature on development and reproduction of Neoseiulus barkeri (Acari: Phytoseiidae) fed on Aleuroglyphus ovatus

Abstract: The effect of five constant temperatures (16, 20, 24, 28 and 32°C) on the development, survival and reproduction of Neoseiulus barkeri Hughes fed on Aleuroglyphus ovatus Toupeau (Acari: Acaridae) was examined in the laboratory at 85% relative humidity. Development time of different immature stages decreased with increasing temperature, total egg-to-adult development time varied from 5.0 ± 0.13 to 17.5 ± 0.29 days. The lower thermal threshold for development was 9.7 ± 2.48°C and the thermal constant from egg to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
22
3
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 18 publications
3
22
3
5
Order By: Relevance
“…This could be due to the higher humidity level applied for E. scutalis. Adult female longevity for N. barkeri (35.6 at 25 C and 27.4 at 35 C) against O. afrasiaticus was close to that reported against A. ovatus (34.6 at 24 C and 23.7 at 32 C) (Xia et al 2012).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This could be due to the higher humidity level applied for E. scutalis. Adult female longevity for N. barkeri (35.6 at 25 C and 27.4 at 35 C) against O. afrasiaticus was close to that reported against A. ovatus (34.6 at 24 C and 23.7 at 32 C) (Xia et al 2012).…”
Section: Discussionsupporting
confidence: 82%
“…A longer life cycle (9.5 days) was recorded when C. negevi fed on T. urticae eggs (Momen 1999). On the other hand, development of N. barkeri immature females was relatively longer in our study (9.6 days at 25 C) than reported when fed on Aleuroglyphus ovatus (7.8 d at 24 C) (Xia et al 2012). These results show that A. ovatus provides N. barkeri with higher reproductive capability than does O. afrasiaticus.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…Influence of Tuta absoluta larvae on adult longevity, survival, oviposition and consumption rate in multiple-mated females of three predatory phytoseiid species 2007). A higher fecundity (30.6 and 30.8 eggs / F) was reported when N. barkeri fed Aleuroglyphus ovatus Toupeau (Acari: Acaridae) at 24 o C and 28 o C (Xia et al, 2012). Kamburov (1971) confirmed poor development and reproduction of A. largoensis when fed on scale crawlers of Aonidiella aurantii (Maskell) and Chrysomphalus aunidum (L.) (Hemiptera: Diaspididae).…”
Section: Discussionmentioning
confidence: 80%
“…For N. barkeri, B. zonata egg diet resulted in a total oviposition lower than those of females fed with nymphs of T. tabaci, T. urticae, Aceria dioscoridis (Soliman and AbouAwad) (Acari: Eriophyidae) (main food) / eggs of E. kiehniella and T. absoluta (factitious food) (Bonde, 1989;Momen, 1995;Momen and El-Laithy, 2007;Momen et al, 2013), while a comparable total number of eggs laid was reported on a diet of A. ovatus (Xia et al, 2012). For A. largoensis, our results clearly show that eggs of B. zonata are an acceptable food resource, promoting oviposition greater than that obtained with diets of tenupalpid and tetranychid mites and pollen grains (Carrillo et al, 2010).…”
Section: Discussionmentioning
confidence: 87%